2014
DOI: 10.1038/ncomms6577
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 regulates EGFR internalization and signalling in tumours

Abstract: Tumours exploit their hypoxic microenvironment to induce a more aggressive phenotype, while curtailing the growth-inhibitory effects of hypoxia through mechanisms that are poorly understood. The prolyl hydroxylase PHD3 is regulated by hypoxia and plays an important role in tumour progression. Here we identify PHD3 as a central regulator of epidermal growth factor receptor (EGFR) activity through the control of EGFR internalization to restrain tumour growth. PHD3 controls EGFR activity by acting as a scaffoldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…The present study aimed to explore the association between PHD3 and HIF2α expression in HCC (under hypoxic conditions). Several studies have demonstrated that PHD3 serves a novel role in the progression and prognosis of cancer (15-24); PHD3 is also able to induce apoptosis and inhibit proliferation in cancer cells (22)(23)(24)(25)(26)(27)(28)(29). To the best of our knowledge, the present study is the first to report that PHD3 overexpression induces apoptosis and inhibits growth and proliferation in HCC cells.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The present study aimed to explore the association between PHD3 and HIF2α expression in HCC (under hypoxic conditions). Several studies have demonstrated that PHD3 serves a novel role in the progression and prognosis of cancer (15-24); PHD3 is also able to induce apoptosis and inhibit proliferation in cancer cells (22)(23)(24)(25)(26)(27)(28)(29). To the best of our knowledge, the present study is the first to report that PHD3 overexpression induces apoptosis and inhibits growth and proliferation in HCC cells.…”
Section: Introductionmentioning
confidence: 59%
“…Given the increasing number of observational studies on PHD3, considerable attention has been focused on the mechanism of PHD3 (17,18,(24)(25)(26)(27)(28). Su et al (18) revealed that PHD3-induced apoptosis is dependent on nerve growth factor by activating caspase-3 in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with previous studies showing that lung carcinomas often co-overexpress EGFR together with TGFα in an autocrine loop to sustain EGFR hyperactivation (46). Interestingly, we have previously shown that PHD3 is a central regulator of EGFR activity through the control of EGFR internalization in glioma (10,11). This endocytic adaptor function of PHD3 in gliomas is independent of the PHD3 hydroxylase activity and HIFs, indicating that PHD3 may impact on the EGFR pathway at different levels and in a tumor entity specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PHDs in tumor growth is incompletely understood. While some studies have demonstrated that PHD deficiency can reduce tumor growth, metastasis or therapy resistance (3)(4)(5)(6), other reports highlight a role of PHDs as tumor suppressors (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%